Effectiveness of acupuncture therapy in patients with lateral epicondylitis - Curbelo Fajardo, Juan Carlos; Cuello Ávila, Jesús; Camero Machín, Julio Cesar; Gómez Carmona, Elizabeth (SCT Proceedings in Interdisciplinary Insights and Innovations, 2023)
A prospective and longitudinal descriptive study was carried out with the objective of evaluating the effectiveness of acupuncture therapy in patients with lateral epicondylitis, treated at the Dr. “León Cuervo Rubio” Hospital from January 2021 to January 2023. The universe was 42 patients with a diagnosis of of lateral epicondylitis who attended the Natural and Traditional Medicine (MNT) consultation and the sample was 37 patients who met certain criteria. The intensity of pain was evaluated, according to the modified Mac Gill scale, and the speed of relief. The set of results was transferred to a Microsoft Excel database, which was expressed as absolute values ​​and percentages. Results: The most prevalent ages were 44-54 years, (51.3%) with 19 patients, with the female sex being the most represented at 56.7% with 21 women. Within the occupations, seamstresses were the most represented with 9 patients, for 24%. Qi Stagnation was present in 64.86% of the sample. Pain was the predominant symptom that was most present in 100% of the patients (37 patients). The intensity of pain before treatment was mostly grade III with 12 patients, representing 32%. At the end of the treatment, 23 patients reported no pain, for a 62% relief. According to the speed of relief, mediate relief predominated with 32 patients, which represented 86.5%. In 32 of the patients studied there were no adverse reactions, for 88%.